Consumer behavior research using data from online games - Kotrba, Vojtěch; Holman, Robert, 1953-; Loužek, Marek, 1975-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2020)
This dissertation thesis is focused on research into the behavior of sports fans when solving an optimization problem in a fantasy sport. Users of fantasy sports show a great motivation to win, which makes them suitable subjects for economic research. Moreover, the data about them is not derived from a laboratory setting but rather a natural environment. The aim is to examine whether users act predominantly rationally, corresponding to the assumptions of neoclassical economics, or whether they use heuristics typical for behavioral economics. The research questions in the empirical chapters focus on whether users consider the players’ appearance, nationality, and the favorite of the match when selecting squads. Both main theories, rational choice and behavioral economics, are introduced before the empirical chapters, taking into account the perspective of historical development. The use of sports environment for economic research is described in more detail, with a special emphasis on the advantages of fantasy sports. Last but not least, the issue of data acquisition for empirical research is discussed. The data used for the research comes from Czech fantasy leagues from the 2015–16 season. The empirical chapters show that users primarily focus on the athletes’ performance, which is always the most important variable in the econometric models that examine the demand for specific athletes. Nevertheless, it turns out that performance is not the only important factor. There is a bias when it comes to the appearance of the athlete, which should be irrelevant to the user. Better-looking soccer players and worse-looking ice hockey players are more in demand for users. There is also a bias for the athlete’s nationality in the Czech soccer league. In general, foreigners are less in demand than domestic athletes. When differentiating between regions, it appears that there is less demand for athletes from Asia and some countries of Eastern Europe.
On the contrary, there is a higher demand for athletes from South America. Moreover, users employ a heuristic related to the favorite of the match to solve the optimization problem. Test models show that the use of this heuristic can bring some advantage to the user, but, overall, it is overused. From the point of view of economic theory, this thesis shows that in addition to a rational interest in the athletes’ performance, users also tend to rely on the help of heuristics. This thesis aims to foster a closer understanding of consumer behavior using data from a natural environment and a demonstration of previously observed biases based on appearance, nationality, and a general presumption of suitability. This thesis is the first to comprehensively use fantasy sports data to examine individual decision-making concerning the concepts of behavioral economics. As for the practical benefits, marketers, managers, and athletes themselves can use these conclusions to improve their communication with their fans and to improve the fans’ experience of sports consumption.
Vedoucí práce: Robert Holman
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: ekonomická teorie [obor disert. práce]; disertace; dissertations